Effects of negative workplace gossip on unethical work behavior in the hospitality industry: the roles of moral disengagement and self-construal. Issue 3 (3rd April 2022) - Guo, Gongxing; Cheng, Bao; Tian, Jian; Ma, Jianfeng; Gong, Chanjuan
ABSTRACT: Following social cognitive theory, this study examines the effects of negative workplace gossip (NWG) on employees' unethical work behavior in the hospitality industry by introducing the mediating role of moral disengagement and moderating role of self-construal. Data were collected with a multi-wave survey approach from five hotels and five restaurants in Shantou, China. The results demonstrate that NWG exerts a significant influence on moral disengagement; this leads to employees' unethical work behavior. Employees' self-construal is a vital boundary condition moderating the detrimental impact of NWG on moral disengagement, as well as the indirect impacts of NWG on unethical work behavior via moral disengagement. The study findings contribute to NWG literature by extending the effects of NWG to unethical work behavior in the hospitality industry and unveiling the internal mechanism linking them. Furthermore, these findings provide a significant boundary condition to grasp when NWG causes moral disengagement and unethical work behavior.